THU0284 Predicting survival in 6240 patients with primary sjÖgren' syndrome (big data sjÖgren project). (15th June 2017) - Brito-Zerόn, P; Acar-Denizli, N; Zeher, M; Rasmussen, A; Li, X; Baldini, C; Gottenberg, J-E; Danda, D; Quartuccio, L; Hernandez-Molina, G; Kruize, AA; Park, S-H; et al.
Abstract : Objectives: To correlate the main features at diagnosis with survival in a multicenter international cohort of patients with primary Sjögren syndrome (SS). Methods: The Big Data Sjögren Project was formed in 2014 to take a "high-definition" picture of the main features of primary SS by merging international SS databases (9302 consecutive patients recruited from 21 countries of the 5 continents) Results: Data about survival at the last visit was available in 6240 patients (5831 women, mean age at diagnosis of 53yrs, 82% White). After a mean follow-up of 7.1yrs, 407 (6%) patients died. Patients who died were more frequently men (10% vs 6%, p=0.004) and White (96% vs 81%, p<0.001), had a higher mean age at diagnosis (64 vs 52yrs. p<0.001) and a higher frequency of abnormal ocular (95% vs 87%, p<0.001) and oral (90% vs 79%, p<0.001) tests in comparison with survivors; sicca symptoms and salivary gland biopsy were unrelated to survival. Immunologically, patients who died showed a higher frequency of RF (52% vs 46%, p=0.039) and cryoglobulins (18% vs 7%, p<0.001). Logistic regression identified as independent variables the age at diagnosis (OR 1.07), male gender (OR 1.77), abnormal ocular (OR 5.79) and oral (OR 2.10) tests, and cryoglobulins (OR 3.10). Time-adjusted multivariate Cox proportional-hazards regression analysis confirmed age at diagnosis (OR 1.12, CI95% 1.10–1.14), male gender (OR 2.12, CI95% 1.36–3.29) and cryoglobulins (OR 2.43, CI95% 1.72–3.42) as independent variables related to death. Conclusions: An older age at diagnosis, male gender and serum cryoglobulins were the principal risk factors associated with death in this large multiethnic cohort of patients with primary SS. Disclosure of Interest: None declared